Methodical and organizational problems of educational software at HEI at evaluating students’ success by testing - Smyetanyuk Л.В. (Journal of Information Technologies in Education (ITE), 2007)
We studied problems of implementation of testing in higher educational institutions using IT. Influence of faculty professional and personal development on the quality of learning and real quality of students training.